2011
DOI: 10.1521/soco.2011.29.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Social Judgments are Influenced By Both Facial Expression and Direction of Eye Gaze

Abstract: In the current study we examined how emotional expressions infl uence two social judgments, approachability and trustworthiness, and how the effect of emotional expression is modulated by the direction of the signaller's eye gaze. For both social judgments, happy faces were judged more positively than all other emotions, while neutral faces were judged more favorably than faces displaying negative emotions. Angry and disgusted faces were given the most negative ratings, signifi cantly more so than sad and fear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 33 publications
9
90
0
Order By: Relevance
“…The timing and direction of gaze can indicate subtle characteristics and states such as dominance or submissiveness, where a person's attention is at the moment, flirtation, interest in beginning a conversation (or desire to avoid one), an invitation for one's conversation partner to take a turn in the dialogue, active listening, and pondering a point [Isbister 2006]. [Willis et al 2011] examined how gaze direction along with facial expression impact the approachability and trustworthiness of faces. They found that direct gaze significantly increased perceived trustworthiness for happy and neutral faces, but decreased it for angry ones.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing and direction of gaze can indicate subtle characteristics and states such as dominance or submissiveness, where a person's attention is at the moment, flirtation, interest in beginning a conversation (or desire to avoid one), an invitation for one's conversation partner to take a turn in the dialogue, active listening, and pondering a point [Isbister 2006]. [Willis et al 2011] examined how gaze direction along with facial expression impact the approachability and trustworthiness of faces. They found that direct gaze significantly increased perceived trustworthiness for happy and neutral faces, but decreased it for angry ones.…”
Section: Related Workmentioning
confidence: 99%
“…In this paper, we evaluate the potential for a straightforward gaze model to convey an NPC attitude toward a player, specifically trust. We focus our proof of concept on conveying trust because it is a fundamental aspect of inter-personal relationships which manifests in numerous non-verbal behaviors [Vrij and Mann 2004;Frith and Frith 2007;Willis et al 2011]. Trust intuitively links to the concept of reputation, which is a popular game mechanic in many RPGs, including Star Wars: The Old Republic, World of Warcraft, and EVE Online.…”
Section: Introductionmentioning
confidence: 99%
“…This behaviourally established relationship suggests that facial expression recognition and inferences of trustworthiness may share some of the same neural mechanisms (Mattavelli, Andrews, Asghar, Towler, & Young, 2012;Said, Haxby, & Todorov, 2011). Importantly, trustworthiness ratings of faces by M A N U S C R I P T (Willis, Palermo, & Burke, 2011;Sutherland, Young, & Rhodes, in press). These are emotions whose recognition, as noted above, is often particularly affected in HD.…”
Section: Sprengelmeyer Et Al 2016 -First Impressions In Huntington'smentioning
confidence: 96%
“…This may be of interest because trustworthiness ratings of faces by neurologically normal perceivers are particularly low when the faces show expressions of disgust and anger (Willis et al, 2011;Sutherland et al, in press). …”
Section: ____________________________________________________________mentioning
confidence: 99%
“…This negativity is recognised by observers; Willis et al 17 found that happy faces were judged more positively than all other emotions, while neutral faces were judged more favourably than faces displaying negative emotions. Angry and disgusted faces were given the most negative ratings, significantly more so than sad and fearful faces.…”
Section: Choice Of Facial Expressionmentioning
confidence: 99%